Effects of Steroid Use On Nutrition Knowledge and Attitude, Body Image Perception, And Cognitive Ability of Bodybuilders - Salleh, Razali Mohamed; Shafiee, Mohd Nur Ikhwan (International Journal of Membrane Science and Technology, 2023)
The use of steroids among bodybuilders is considered typical by many, probably due to the tendency to become exceptionally lean and masculine. However, as anabolic steroids may cause adverse effects, this may make steroid-using bodybuilders vulnerable to unhealthy eating and perception of body image. Therefore, a study was conducted to determine whether steroid-using bodybuilders have different nutrition knowledge and attitude, body image perception and cognitive ability compared to their non-steroid-using counterparts. Fourteen amateur bodybuilders, including seven self-claimed steroid users, voluntarily agreed to participate in this study. Nutrition knowledge and attitude were determined using established self-administered questionnaires. While body image perception and cognitive ability were assessed using the Adonis Complex questionnaire and mental rotation test, respectively. When comparing steroid and non-steroid users, there was no difference in nutrition knowledge and attitude. However, both groups significantly differed in body image perception (p= 0.048) and cognitive ability MRT (p= 0.039). Even though these findings show significant impacts of steroid use on certain